PARTISIPASI MASYARAKAT DALAM PENYUSUNAN REGULASI PENANGGULANGAN BENCANA: PERSPEKTIF HUKUM ADMINISTRASI NEGARA - arifin, firdaus (Program Studi Magister Hukum Universitas Malikussaleh, 2024)
The increasing frequency and intensity of disasters in Indonesia demands a reformulation of administrative law in disaster management. The gap between the existing legal framework (das sollen) and its implementation on the ground (das sein) hinders the effectiveness of disaster response. This research aims to analyze the need for reformulation of administrative law to improve the effectiveness of disaster management in Indonesia. Using a qualitative approach with a comparative case study design, this research combines legal document analysis, semi-structured interviews, and comparative analysis of international practices. The research results show that the Indonesian legal framework lacks flexibility in accommodating the need for rapid decision-making during emergency situations, as well as weak inter-agency coordination and local capacity. Reformulation of administrative law is needed to balance operational flexibility and legal accountability, as well as integrate disaster risk management into development planning. The implications of this research include recommendations for revising Law No. 24 of 2007, improving inter-agency coordination, strengthening local capacity, and adopting a participatory approach in disaster management.